The Density Value of Mixing Water and Cooking Oil Using an Emulsifier (Tween 20) - Budhi Rahardja, Istianto; Basyir Rantawi, Azhar; Saputra, Hendra; Oktavia Pambudi, Dian; Naufal Rangga Gumilang, Raden; Afni Safitri, Nur; Mahadewa, Mirza; Meutia Tari, Eka; Ilmar Ramadhan, Anwar; Susanto, Edy (DINAMIS, 2024)
Water and cooking oil are fluids that we often encounter in our daily lives and are often needed. Water is polar while cooking oil is non-polar, so in uniting the two fluids an emulsifier (Tween 20) is used to mix them. The aim of this research is to combine polar and non-polar fluids. Emulsifier (Tween 20) is used as a polysorbate surfactant (mixing agent) for the two fluids and can mix perfectly. The combined water and oil are mixed using a mixing stirrer with a speed of 100-200 rpm, a temperature of 70â°C, within 1 hour. To obtain a fluid density value by providing heating from 30â°C-90â°C, then inserting it into a 25 ml volumetric flask and weighing it. After mixing, a white hybrid fluid will be produced, and it will separate again when the fluid is at room temperature.